2010
DOI: 10.1177/1534735410379013
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin Monomethyl Ether Enhances the Killing of Ultrasound on Osteosarcoma Cells Involving Intracellular Reactive Oxygen Species and Calcium Ion Elevation

Abstract: Objective: The present study aims to investigate the possible mechanisms of hematoporphyrin monomethyl ether (HMME) enhancing the cytotoxicity of ultrasound in osteosarcoma cells. Methods: Osteosarcoma cell line UMR-106 was treated by HMME and ultrasound radiation, with the HMME concentration kept at 20 mg/mL and ultrasound radiation for 10 seconds at the intensity of 0.5 W/cm 2 . Cell proliferation was investigated at 12, 24, 36, and 48 hours using MTT assay after ultrasound and HMME treatment. Ultrastructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is well known that activation of sonosensitizers can induce ROS production in cells[ 8 , 27 ] and the high levels of ROS can damage the mitochondrial membranes and oxidize mitochondrial proteins, leading to depletion of antioxidants and formation of mitochondrial permeability transition pore as well as apoptosis [ 18 , 28 ]. In addition, high levels of ROS can convert into H 2 O 2 and other toxic metabolites that release cytochrome C to activate caspase cascade, and finally lead to apoptosis[ 29 , 30 ]. Given that ultrasound alone moderately inhibited osteosarcoma cell proliferation and induced tumor cell apoptosis the mechanical effect of ultrasound may directly damage cell membranes and enhance cell membrane permeability[ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that activation of sonosensitizers can induce ROS production in cells[ 8 , 27 ] and the high levels of ROS can damage the mitochondrial membranes and oxidize mitochondrial proteins, leading to depletion of antioxidants and formation of mitochondrial permeability transition pore as well as apoptosis [ 18 , 28 ]. In addition, high levels of ROS can convert into H 2 O 2 and other toxic metabolites that release cytochrome C to activate caspase cascade, and finally lead to apoptosis[ 29 , 30 ]. Given that ultrasound alone moderately inhibited osteosarcoma cell proliferation and induced tumor cell apoptosis the mechanical effect of ultrasound may directly damage cell membranes and enhance cell membrane permeability[ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that HMME combined with ultrasonic irradiation obviously enhanced the intracellular ROS production 39 and the expression of Bax, caspase-3 and caspase-9 proteins 40 , and also displayed significant improvement on the suppression of cell viability and the induction of cell apoptosis 41 . Recent studies on human leukemia U937 cells 32 and osteosarcoma 42 revealed that HMME combined with ultrasonic irradiation might be a promising approach for cancer therapy. PpIX is a novel HPD and displays stronger anticancer activities than HP under the same ultrasonic condition because that it is much easier to be taken up by cancer cells 43 .…”
Section: Sonosensitizersmentioning
confidence: 99%
“…Ultrasound is known to promote membrane permeability, thus increasing intracellular drug accumulation. Previous studies have suggested that the mechanisms by which ultrasound enhances the cytotoxicity of chemotherapy drugs include increased generation of reactive oxygen species [10,11], intracellular drug accumulation [12,13], and cell membrane permeability [14,15,16]. The combined therapy concentration and sufficient exposure time were crucial to the chemotherapeutic efficacy in our study.…”
Section: Discussionmentioning
confidence: 61%